The Power of Collaboration: Learning English through Activities and Peer Feedback - Syahmina, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
This article explores how collaborative learning changes the course of English language acquisition through group activities and peer feedback. In the context of emerging educational paradigms, which have steadily shifted from teacher-centred methods to more student-centred approaches, collaborative learning appears to be one such dynamic framework that fosters interaction, communication, and critical thinking among learners. The role of group activities in language learning aligns closely with Vygotsky’s sociocultural theory, as these activities enable students to practice and internalize new language forms within interactive social settings. The article elaborates on several advantages of collaborative learning: enhanced language skills, increased motivation and improved interpersonal skills. Some of the problem areas that usually present themselves as tricky around collaborative learning are those to do with unequal participation and different proficiency levels. The strategic solutions, educators can constructively foster a collaborative classroom that then enables students and prepares them for real-world communication. introducing collaborative practices into the learning of the English language would therefore enhance not only a better educative experience but also one of community and shared growth among learners.